Faith, science, and the wager for reality: Meillassoux and Ricœur on post-Kantian realism - Aspray, B (Taylor and Francis, 2023)
This article compares two attempts to return to realism after Kant’s ‘Copernican Revolution’. Quentin Meillassoux, representing the ‘speculative realism’ school, rejects both Kantian and post-Kantian idealism in favour of a materialism based on the epistemology of the modern sciences. But Meillassoux is unaware of the element of choice in his philosophical position, and he does not solve the essential problem posed by idealism which concerns the place of the subject in being. Ricœur, on the other hand, sublates Kant by a deeper embrace of finitude that leads to the self-displacement of the subject, and a ‘Second Copernican Revolution’, one that he freely admits can only be arrived at by Jaspersian ‘Philosophical Faith’. The article concludes by showing how crossing the border into theological faith offers a virtue-ethical perspective on the question of realism and idealism: it is in fact the choice between a childlike humility that receives reality as it is, and an arrogant self-positing that puts the subject in the position of God.